2022
DOI: 10.1007/s00106-022-01232-3
|View full text |Cite
|
Sign up to set email alerts
|

Sprachverstehen im Störschall—Überlegungen zur ökologisch validen Bewertung der Kommunikationsfähigkeit mit Cochleaimplantat

Abstract: Background Nowadays, cochlear implant (CI) patients mostly show good to very good speech comprehension in quiet, but there are known problems with communication in everyday noisy situations. There is thus a need for ecologically valid measurements of speech comprehension in real-life listening situations for hearing-impaired patients. The additional methodological effort must be balanced with clinical human and spatial resources. This study investigates possible simplifications of a complex measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Compared with age-specific reference data for the same spatial signal and noise configurations [ 32 ], the present results demonstrate that some CI users are able to perform similar to normal-hearing listeners. Thus, despite the fact that studies often overestimate the performance of CIs due to the experimental design [ 40 , 41 ], we conclude that FF provides a tool that significantly reduces hearing deficits in some situations.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Compared with age-specific reference data for the same spatial signal and noise configurations [ 32 ], the present results demonstrate that some CI users are able to perform similar to normal-hearing listeners. Thus, despite the fact that studies often overestimate the performance of CIs due to the experimental design [ 40 , 41 ], we conclude that FF provides a tool that significantly reduces hearing deficits in some situations.…”
Section: Discussionmentioning
confidence: 66%
“…Although hearing tests in noise are becoming more relevant in everyday clinical practice, their ecological validity needs to be improved [ 41 ]. Several studies have shown that fluctuating interfering signals or competing talkers [ 45 ] can best reflect everyday situations [ 42 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation